Encyclopedia of politics : the left and the right - Carlisle, Rodney P.; Gale Group (Thousand Oaks, Calif. : Sage Publications, 2005)
This two-volume Encyclopedia of Politics: The Left and the Right contains over 450 articles on individuals, movements, political parties, and ideological principles, with those usually thought of as left in the left-hand volume (Volume 1) and those considered on the right, in the right-hand volume (Volume 2)
Obsahuje bibliografii a rejstřík
Elektronická reprodukce.
Keywords: politologie; pravice; levice; political science; right (political science); left (political science); encyklopedie; elektronické knihy; e-knihy online; encyclopedias; electronic books; e-books online